Adaption and Evaluation of a Self-Efficacy Intervention for Parental Feeding Practices. Issue 1 (10th October 2022) - Vogel, Hannah; ten Hoor, Gill; Mergelsberg, Enrique; Mullan, Barbara
Background: A healthy parental feeding program consisting of six sequential modules was developed to improve parental feeding behaviours. The six modules focusing on various parental feeding behaviours were found to be moderately effective in changing behaviour. In this study, one of those modules (the self-efficacy module) was systematically adapted and evaluated using Intervention Mapping (IM). Methods: In a literature review (Study 1), the relevance of self-efficacy as a determinant for parental feeding habits was examined. In study 2, the behaviour change techniques used in the original healthy parental feeding program were analysed and adapted to fulfil the related parameters of effectiveness. In study 3, the effectiveness of the new module was pilot-tested among parents ( N = 27). Parents received either the original self-efficacy module (group 1), the adapted self-efficacy module (group 2), or no additional module (group 3/control-group). Parental self-efficacy was measured at baseline, post-intervention and at one-week follow-up. Results: In study 1, self-efficacy was identified as a relevant (i.e., important and changeable) determinant for parental feeding habits. In study 2, parameters for effectiveness of the used behaviour change techniques were added where necessary, and texts were changed to improve understanding. In study 3, both the original and new module appeared to increase self-efficacy compared to the no-intervention control group. Discussion: This study was an attempt to adapt existing behaviour change programs based on theory and evidence. However, we were not successful in changing self-efficacy more as compared to the original module.